2020
DOI: 10.1002/eat.23269
|View full text |Cite
|
Sign up to set email alerts
|

Weight suppression and weight maintenance following treatment of anorexia nervosa

Abstract: Objective: The value of weight suppression (WS) in predicting the course of anorexia nervosa (AN) is uncertain. The objective of this study was to determine, using data from a previously published study, whether patients who remain weight suppressed following restoration to a minimally normal weight are at greater risk for relapse.Method: Following weight restoration, 93 women with AN were randomly assigned to receive fluoxetine or placebo along with cognitive behavioral therapy for 1 year. WS (highest adult w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…The predictors were classified into three groups: biological predictors, psychological predictors, and ED-related predictors. Of the 19 studies included in this review, 8 excluded patients with a BMI below 18.5 kg/m 2 at discharge [ 12 , 16 , 30 , 32 , 33 , 37 , 38 , 39 ]. Another eight studies had not excluded patients with BMI below 18.5 kg/m 2 , but the variability of BMI at discharge indicated that potentially a minor subgroup of these patients was not in complete remission [ 23 , 25 , 26 , 31 , 34 , 35 , 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictors were classified into three groups: biological predictors, psychological predictors, and ED-related predictors. Of the 19 studies included in this review, 8 excluded patients with a BMI below 18.5 kg/m 2 at discharge [ 12 , 16 , 30 , 32 , 33 , 37 , 38 , 39 ]. Another eight studies had not excluded patients with BMI below 18.5 kg/m 2 , but the variability of BMI at discharge indicated that potentially a minor subgroup of these patients was not in complete remission [ 23 , 25 , 26 , 31 , 34 , 35 , 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 13 studies concerned biological predictors of relapse, and 8 of these described BMI or weight as a predictor of relapse [ 24 , 28 , 30 , 31 , 32 , 34 , 39 ]. Only one of these studies had a high [ 31 ], most others moderate, and only one had a low quality of evidence [ 39 ]. The studies differed in design, BMI measurement time points, and whether weight or/and BMI were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Greater current weight suppression has been found to predict future onset of AN (11) and has been associated with faster and greater weight normalization during inpatient treatment of AN [e.g., (12,13)]. However, there are mixed findings regarding long-term treatment outcomes, with reports of higher weight suppression at the time of lowest BMI being associated with higher BMI at 6-to 18-year follow-up (14), and higher weight suppression at discharge predicting better weight maintenance at 1-year follow-up (15), but also reports showing no effect of weight suppression at discharge on weight maintenance at 1-year follow-up (16).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on inpatient samples specifically have tended toward examining predictors of outcome unrelated to treatment (e.g., age of onset, comorbidities, family support) and report overall prognosis categorically [42][43][44][45][46][47]. Fewer have studied continuous outcomes, such as weight, symptoms, and overall clinical impairment over time [13,23,38,48,49], and these have generally been limited to short-term follow up [13,19,49] or to a single assessment point [23,25,34]. Together, these studies suggest that higher BMI at discharge and shorter duration of illness are important factors in the course of AN.…”
Section: Introductionmentioning
confidence: 99%